Aligner Tones Software Improve Measurement Precision In The Process of Balinese Gamelan - Made Sudarma; Ni Wayan Sri Ariyani; I Nyoman Adiputra (Institute of Advanced Engineering and Science, 2013)
In the making process of Balinese gamelan, the tone arrangement highly depends on aligner sense and feeling which generally performed by the gamelan’s craftsman himself. Each aligner has his way of aligning with different standard of tone. Tunings process is still based on the sensitivity of the ear and the feelings of the gamelan craftsmen so that the precision of tone can not be achieved. The unavailable of a standard measuring instruments tone used in the tuning process lead to the production process gamelan in Bali takes a long time. To solve these problems, a study conducted by utilizing information technology in the computer - software engineering approach.Besides, to anticipate the limitation of human resources in the field of alignment and to maintain the consistency of the gamelan’s tone in the long period of time it is in need for the touch of information technology in the form of software. The software to analyze the frequency of gamelan’s base tone in order to get the result of the tone in the strip of gamelan which is measurable and in accordance with the expectation. The software is intended will be able to perform the test tone as desired by the buyer. Thus the tone of the achievements obtained quickly, accurately correspond to the reference tone. It also means that the program contributed significantly to the preservation of Balinese culture can be done.DOI:http://dx.doi.org/10.11591/ijece.v3i1.1481